Self‐Reliant Citizens, Market Deregulation, and Labour Flexibility: The Case of Finnish Entrepreneurship Strategy (2000–2022) - Bobba, Anuhya (Wiley, 2025)
Since 2000, entrepreneurship has come to occupy a central position in Finnish policy, praised not simply as a form of work but as a disciplinary ethos that places increased responsibility on the individual for employment and welfare. From decreased labour productivity, depleting labour supply, insufficient foreign investment, and unemployment to climate deterioration and poverty, entrepreneurship will allegedly offer a solution, if necessary conditions for entrepreneurial development and success are enabled by government intervention. However, the reality of entrepreneurship differs starkly from policy expectations and predictions. Instead, it is a largely precarious form of work that involves financial risk and with monthly earnings subordinate to the national average. To explore this inconsistency, I take inspiration from Bacchi's (2009) 'what's‐the‐problem‐represented‐to‐ be?' (WPR) framework to analyse a total of six strategy documents and five implementation documents from 2000 to 2022. I argue that the problem representations embedded in entrepreneurship policies since the second Lipponen cabinet do not permit
a broader critique of entrepreneurship, the very subject of these policies, and instead advocate for a series of measures that prioritise market deregulation and strip important labour protections.